Tabungan Easy Wadi’ah Menjadi Primadona di BSI KCP. Kampung Pajak - Rica Rahim Lubis (Jurnal Perbankan Syariah, 2025)
This study aims to analyze why the Easy Wadi’ah Savings product has become the leading choice at PT. Bank Syariah Indonesia Tbk Kampung Pajak Branch Office. This product is based on the wadi’ah yad dhamanah contract, which is free from riba elements and adheres to Islamic financial principles. The research employed a descriptive qualitative approach through direct observation, interviews, and documentation during the internship period. The findings reveal that this savings product is highly favored by the public due to its ease of transactions, zero administrative fees, and accessibility via the BSI Mobile application. Other contributing factors include friendly customer service, product socialization via webinars, and increasing public awareness of Islamic financial services. These findings highlight the importance of innovation based on Islamic values in strengthening the competitiveness of Islamic banking products in the modern era.